Low back pain, obesity, and inflammatory markers: exercise as potential treatment - Cruz Fernandes, Isabela Maia da [UNESP]; Pinto, Rafael Zambelli; Ferreira, Paulo; Lira, Fabio Santos [UNESP] (Korean Soc Exercise Rehabilitation, 2018)
Low back pain is a health issue with significant impact to patients and society. This narrative review aims to synthesize the relationship between obesity, low-grade inflammation and low back pain. It is known that a sedentary lifestyle is a risk factor for obesity and related disorders. The adipose tissue of obese people secretes a range of cytokines of character pro-and anti-inflammatory, with many molecular effects. In addition, pro-inflammatory cytokines are sensitizers of C-reactive protein (CRP), a marker of acute inflammation that can be linked to the musculoskeletal pain sensation individuals with back pain. Another inflammatory marker deserves mention, prostaglandin E-2. Prostaglandin E-2 is important in the process of triggering actions such as pyrexia, sen-sation of pain and inflammation, which are exhibited in low back pain condition. The potential for exercises and physical activity to control these mediators and act as a preventative measure for back pain are important because they work as a nonpharmacological strategy to this target audience. There are two types of exercise discussed in this review, the moderate-intensity continuous training and high-intensity interval training.
Keywords: Low back pain; Obesity; Sedentary lifestyle; C-reactive protein; Prostaglandins